Images in medicine: torus palatinus - Amir Hanafi; Richard Alweis (Greater Baltimore Medical Center, 2019)
A 56 year old African-American female with history of well-controlled hypertension and hyperlipidemia presented to the office for an annual physical examination. She did not have any complaints. She reported being compliant with her medications, exercised daily at her local gym, and maintained a low salt diet. She visits her dentist every 6 months and has had a few fillings in her premolars in the past. On physical examination, her vital signs were normal and the entirety of her physical examination was normal with the exception of her oropharynx. Throat examination revealed a 2 × 1 cm midline hard palate swelling that was bony hard in consistency and covered by normally appearing oral mucosa. It was diagnosed as a torus palatinus. The patient was unaware of its presence and denied being informed about it by her dentist on any visit. She was also educated about the diagnosis and safety-netted by being informed about red-flags that would prompt investigation such as change in size or shape.